Urban land use planning for economic growth. - Collier, Paul; Glaeser, Edward; Venables, Tony; Manwaring, Priya (My University, 2020)
Land use planning plays a crucial role in improving the productivity, liveability and sustainability of developing cities. Drawing on successful reforms from developed and developing countries, this paper explores the trade-offs associated with designing and enforcing land use plans and regulations in the context of rapid and often informal urban development.
Keywords: Stadtwachstum; Flächennutzungsplanung; Stadtentwicklungsplanung; Schwellenland; Entwicklungsland; Industrieland; Stadtstruktur; Baulandentwicklung; Stadtentwicklungspolitik; Privatinvestition; Kooperation; Partizipation; Finanzierung; Fallbeispiel; Internationaler Vergleich